2020
DOI: 10.3389/fchem.2020.00358
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Sufficient Nanoplatform for Chemo-Sonodynamic Therapy of Hypoxic Tumors

Abstract: Modulation of hypoxia is an essential factor for enhancing the effects of antitumor therapies, especially sonodynamic therapy and chemotherapy. To improve the efficacy of combination therapy by reversing the hypoxic tumor microenvironment, we developed shell-core structured PPID-NPs, which were designed with a polymer shell onto the sonosensitizer and a chemotherapeutic drug were loaded and a perfluorocarbon core loaded with oxygen. The perfluorocarbon core provides sufficient oxygen not only for causing the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
(38 reference statements)
0
29
0
Order By: Relevance
“…Many recent preclinical studies of potential liquid perfluorocarbon emulsions are aimed at theranostic ( i.e., therapy and diagnostic) capabilities and alternative applications. The clinical and preclinical studies include drug delivery ( Al Rifai et al, 2020 ), adjuvants for blood-brain barrier opening ( Peng et al, 2018 ), anti-ischemics and antihypoxants ( Leese et al, 2000 ; Noveck et al, 2000 ; Hill et al, 2002 ; Kachalina et al, 2007 ; Kligunenko et al, 2007 ; Moroz et al, 2007 ; Yermolenko et al, 2007 ; Culp et al, 2019 ; Huang et al, 2020 ), liquid ventilation therapy ( EU/3/20/2383, 2021 ; EU/3/20/2361, 2021 ), radiological contrast agents ( Mattrey et al, 1987a ; Mattrey et al, 1987b ; Bruneton et al, 1988 ; Mattrey et al, 1988 ; Mattrey, 1989 ), and thermal enhancement for focused ultrasound ablation ( Zhang et al, 2011 ; Desgranges et al, 2019 ; Lorton et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many recent preclinical studies of potential liquid perfluorocarbon emulsions are aimed at theranostic ( i.e., therapy and diagnostic) capabilities and alternative applications. The clinical and preclinical studies include drug delivery ( Al Rifai et al, 2020 ), adjuvants for blood-brain barrier opening ( Peng et al, 2018 ), anti-ischemics and antihypoxants ( Leese et al, 2000 ; Noveck et al, 2000 ; Hill et al, 2002 ; Kachalina et al, 2007 ; Kligunenko et al, 2007 ; Moroz et al, 2007 ; Yermolenko et al, 2007 ; Culp et al, 2019 ; Huang et al, 2020 ), liquid ventilation therapy ( EU/3/20/2383, 2021 ; EU/3/20/2361, 2021 ), radiological contrast agents ( Mattrey et al, 1987a ; Mattrey et al, 1987b ; Bruneton et al, 1988 ; Mattrey et al, 1988 ; Mattrey, 1989 ), and thermal enhancement for focused ultrasound ablation ( Zhang et al, 2011 ; Desgranges et al, 2019 ; Lorton et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The IR780@PLGA nanoparticles were prepared by a single emulsion evaporation method based on our group’s previous studies ( Wang L et al, 2018 ; Chen et al, 2020 ; Huang et al, 2020 ). In brief, 50 mg of PLGA and 1 mg of IR780 were completely dissolved in 2 ml of chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…However, few studies have reported IR780 as a sonosensitizer to combat MDR bacterial infection. Our previous study showed that sonosensitizer IR780-based and oxygen-sufficient drug-loaded nanoparticles can reverse the hypoxic tumor microenvironment and improve the efficacy of chemosonodynamic antitumor therapy ( Huang et al, 2020 ). In this study, we first reported IR780-based PLGA nanoparticles (IR780@PLGA) for antibacterial SDT of methicillin-resistant Staphylococcus aureus (MRSA) myositis.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges associated with sonosensitizers include getting them accumulated at the site of infection at adequate concentration, the hypoxic microenvironment in biofilms, which reduces ROS generation, and rapid decline in oxygen concentration at the site receiving SDT (Figure ). Approaches to deliver or generate oxygen in situ have been explored to enhance sonodynamic therapy . Sun and colleagues reported a nanoparticle-based carrier, which can be triggered to activate the sonosensitizer for ROS production.…”
Section: Sonosensitizers and Delivery Systemsmentioning
confidence: 99%
“…119 Approaches to deliver or generate oxygen in situ have been explored to enhance sonodynamic therapy. 120 Sun and colleagues reported a nanoparticle-based carrier, which can be triggered to activate the sonosensitizer for ROS production. The nanoplatform Pd@Pt with the sonosensitizer T790 was used, which had catalytic oxygen and ROS.…”
Section: Sonosensitizers and Delivery Systemsmentioning
confidence: 99%